Cloud based networking solutions of Robi Axiata Ltd: a solution or a stumbling block - Azim, Syed Tausif (BRAC University, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2017.